Spatio-temporal patterns of river water quality in the semiarid northeastern Brazil - Freire, Letícia Lacerda (2021)
Non-perennial rivers have attracted significant attention due to the progressive increase in water demand and pollution, river engineering side effects and climate change. The present study investigates the interannual, seasonal and spatial variability of nine water quality variables (pH, colour, turbidity, biochemical oxygen demand, total phosphorus, total inorganic nitrogen, chlorophyll-a, total solids and thermotolerant coliforms) from 93 monitoring river sites distributed over 11 watersheds in the highly populated Brazilian semiarid region. Shapiro–Wilk and Kruskal–Wallis tests were applied for assessing data normality and statistical differences, respectively. Additionally, principal component analysis (PCA) was performed for comparison between temporal and spatial data sets, while the Standardized Precipitation Index (SPI) was used to characterize meteorological drought. The results revealed that spatial variability is more evident than temporal variability. In the temporal scale, the interannual variability is more relevant than the seasonal one. The discharge of wastewater seems to attenuate a seasonal hydrological effect on water quality. There is a deterioration of water quality in most watersheds in the drier years, even in the rainy season. This is especially for colour,